Critical theory today : a user-friendly guide - Tyson, Lois, 1950- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2015)
"This thoroughly updated third edition of 'Critical Theory Today' offers an accessible introduction to contemporary critical theory, providing in-depth coverage of the most common approaches to literary analysis today, including: feminism; psychoanalysis; Marxism; reader-response theory; New Criticism; structuralism and semiotics; deconstruction; new historicism and cultural criticism; lesbian, gay, and queer theory; African American criticism and postcolonial criticism."--
1. Everything you wanted to know about critical theory but were afraid to ask -- 1. Psychoanalytic criticism -- 3. Marxist criticism -- 4. Feminist criticism -- 5. New criticism -- 6. Reader-response criticism -- 7. Structuralist criticism -- 8. Deconstructive criticism -- 9. New historical and cultural criticism -- 10. Lesbian, gay, and queer criticism -- 11. African American criticism -- 12. Postcolonial criticism -- 13. Gaining an overview.
Includes bibliographical references and index.
Keywords: Criticism